2001
DOI: 10.1034/j.1600-051x.2001.028010955.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in smokers and non‐smokers: intra‐oral distribution of pockets

Abstract: The present study indicates that cigarette smoking is a factor associated with deeper periodontal pockets and an intra-oral distribution that is suggestive of a local effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 31 publications
10
68
2
4
Order By: Relevance
“…Studies that used periodontal probing depth as a diagnostic criterion for periodontal disease have reported that cigarette smokers had both a significantly greater pocket frequency and deeper probing depth compared to non-smokers (Horning et al 1992, Bergström 1989, Faddy et al 2000, Van der Weijden et al 2001, Susin et al 2005. In general agreement with these reports a significant association between tobacco smoking and periodontal probing depth was observed (Study II).…”
Section: Periodontal Pocketssupporting
confidence: 81%
“…Studies that used periodontal probing depth as a diagnostic criterion for periodontal disease have reported that cigarette smokers had both a significantly greater pocket frequency and deeper probing depth compared to non-smokers (Horning et al 1992, Bergström 1989, Faddy et al 2000, Van der Weijden et al 2001, Susin et al 2005. In general agreement with these reports a significant association between tobacco smoking and periodontal probing depth was observed (Study II).…”
Section: Periodontal Pocketssupporting
confidence: 81%
“…The percentage at T2 were comparable with baseline registration and in accordance with previous findings demonstrating a high percentage of PD ≥ 5 mm in single‐rooted teeth in smokers (van der Weijden et al. 2001). Interestingly, the results show slightly different site‐specific treatment outcomes following APT and SPT, indicating altered local tissue responses to cigarette smoking during APT compared with SPT.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is one of the most important risk factors for periodontal disease 13,14) . In this study, subjects who smoked had a significantly higher risk not only for having deep periodontal pockets, but also for having decayed teeth, compared with nonsmoking subjects.…”
Section: Discussionmentioning
confidence: 99%